2005
DOI: 10.1103/physrevc.72.044307
|View full text |Cite
|
Sign up to set email alerts
|

Charge and matter distributions and form factors of light, medium, and heavy neutron-rich nuclei

Abstract: Results of charge form factors calculations for several unstable neutron-rich isotopes of light, medium, and heavy nuclei (He, Li, Ni, Kr, Sn) are presented and compared to those of stable isotopes in the same isotopic chain. For the lighter isotopes (He and Li) the proton and neutron densities are obtained within a microscopic large-scale shell-model, while for heavier ones Ni, Kr, and Sn the densities are calculated in deformed self-consistent mean-field Skyrme HF+BCS method. We also compare proton densities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
137
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 75 publications
16
137
0
1
Order By: Relevance
“…We extend the analysis of nuclear sizes presented in Ref. [22] by performing a more systematic study of a larger set of exotic nuclei and calculating also neutron skin thicknesses. The calculated charge rms radii are compared with the laser or muonic atoms spectroscopy measurements of isotope shifts performed on Sn [37][38][39][40], Ni [41,42], and Kr [43] isotopes.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…We extend the analysis of nuclear sizes presented in Ref. [22] by performing a more systematic study of a larger set of exotic nuclei and calculating also neutron skin thicknesses. The calculated charge rms radii are compared with the laser or muonic atoms spectroscopy measurements of isotope shifts performed on Sn [37][38][39][40], Ni [41,42], and Kr [43] isotopes.…”
Section: Introductionmentioning
confidence: 97%
“…[17,18]) or the Hartree-Fock-Bogoliubov (HFB) method including pairing correlations [19][20][21][22][23][24]. The latter predicts well the monotonic increase of the neutron skin thickness for different chains of isotopes up to the drip line [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therein densities obtained from no-core shell model calculations [5,6] also were used. With the He isotopes, they found that the charge density of 6 He differed from that of 4 He but that of 8 He was not significantly different to that of 6 He. They also noted that the proton density does extend far with increasing neutron number.…”
mentioning
confidence: 96%
“…We choose some spherical medium and heavy Ni (A=74-84) and Sn (A=124-152) isotopes (considered also in Refs. [19,20]) because, first, they are primary candidates to be measured at the upcoming experimental facilities, and second, for them several predictions have been made concerning the nuclear skin emergence. In addition, we present some results for a chain of Pb (A=202-214) isotopes being inspired by the significant interest (in both experiment [21,22,23] and theory [24,25,26,27]) to study, in particular, the neutron distribution of 208 Pb and its rms radius.…”
Section: Introductionmentioning
confidence: 99%